Performance of an ambulatory electroencephalogram sleep monitor in patients with psychiatric disorders. (28th December 2020) - Miyata, Seiko; Iwamoto, Kunihiro; Banno, Masahiro; Eguchi, Junichi; Kaneko, Satoshi; Noda, Akiko; Ozaki, Norio
Abstract: Key clinical symptoms observed among individuals with psychiatric disorders include difficulty falling asleep or maintaining sleep, poor sleep quality and nightmares. Those suffering from sleep disorders often present with symptoms of discontent with regard to sleep quality, timing and quantity, and these symptoms have an adverse impact on function and quality of life. A minimally invasive technique would be preferable in patients with psychiatric disorders, who tend to be sensitive to environmental change. Accordingly, we evaluated the performance of Zmachine Insight Plus, an ambulatory electroencephalography sleep monitor, in patients with psychiatric disorders. One hundred and three patients undergoing polysomnography were enrolled in this study. Zmachine Insight Plus was performed simultaneously with polysomnography. Total sleep time, sleep efficiency, wake after sleep onset, rapid eye movement (REM) sleep, light sleep (stages N1 and N2) and deep sleep (stage N3) were assessed. Total sleep time, sleep efficiency, wake after sleep onset, REM sleep duration and non‐REM sleep duration of Zmachine Insight Plus showed a significant correlation with those of polysomnography. Lower sleep efficiency and increased frequency of waking after sleep onset, the arousal index and the apnea–hypopnea index on polysomnography were significantly associated with the difference in sleep parameters between the two methods. Among patients with psychiatric disorders who are sensitive to environmental change, Zmachine Insight Plus would be a useful technique to objectively evaluate sleep quality.